Attitudes of patients’ relatives in the end stage of life about do not resuscitate order - Tajari, Mozhdeh (J Family Med Prim Care, 2018)
INTRODUCTION AND OBJECTIVE: The do not resuscitate (DNR) order is a decision taken by the patient or other people about medical care in the end stages of life to prevent resuscitation from causing cardiac or respiratory arrest. This study was conducted to evaluate the attitudes of patients’ relatives in the end stages about DNR order. MATERIALS AND METHODS: In a cross-sectional study, 150 relatives of patients who had been prescribed DNR orders were included in the educational hospitals affiliated to the Kermanshah University of Medical Sciences. The data collection tool was a researcher-developed questionnaire consisting of 29 attitudes questions related to DNR orders. The data were collected and analyzed in the SPSS software version 19 using descriptive tests. RESULTS: According to the results of present study, although the relatives of pationts consider doctors thoroughly responsible for making decision related with DNR, and follow their order either way, they strongly disagree with a single doctor making individual decision in this domain. They believe that the patient and their relatives should be engaged in this decision. Although most participants tended to stay as close as possible to the patients and engage in patient care. CONCLUSION: Given that there are a few studies in Iran on the attitudes of patients and their relatives about DNR, and there are no specific rules and guidelines in this regard. It is recommended that further studies be conducted on the subject. Engaging of patients and families in this important decision is necessary.